1993
DOI: 10.1126/science.8094261
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in Signal Transduction Determined by γ Subunits of Heterotrimeric G Proteins

Abstract: Various heterotrimeric guanine nucleotide-binding proteins have been identified on the basis of the individual subtypes of their alpha subunits. The beta gamma complexes, composed of beta and gamma subunits, remain tightly associated under physiological conditions and have been assumed to constitute a common pool shared among various guanosine triphosphate (GTP)-binding (G) protein heterotrimers. Particular alpha and beta subunit subtypes participate in the signal transduction processes between somatostatin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
176
4
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(187 citation statements)
references
References 20 publications
6
176
4
1
Order By: Relevance
“…Because this ␥ subunit is widely expressed (69), these observations suggest that cells containing ␥ 11 could use dimers containing ␥ 11 to couple ␣ subunits to receptors, allowing receptors to activate ␣ subunits without inducing effects on downstream ␤␥ targets. Taken further, this argues that receptor activation may release specific ␤␥ dimers, a concept that gains experimental support from biochemical experiments (31,(71)(72)(73), antisense mRNA experiments (74,75), small interfering RNA experiments (76), and data obtained with knockout mice (77).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Because this ␥ subunit is widely expressed (69), these observations suggest that cells containing ␥ 11 could use dimers containing ␥ 11 to couple ␣ subunits to receptors, allowing receptors to activate ␣ subunits without inducing effects on downstream ␤␥ targets. Taken further, this argues that receptor activation may release specific ␤␥ dimers, a concept that gains experimental support from biochemical experiments (31,(71)(72)(73), antisense mRNA experiments (74,75), small interfering RNA experiments (76), and data obtained with knockout mice (77).…”
Section: Discussionmentioning
confidence: 90%
“…Examples include the original antisense experiments performed in GH3 cells, suggesting that specific ␤␥ isoforms couple to muscarinic and somatostatin receptors (74,75,88), results from mice in which the ␥ 7 gene has been ablated, showing that loss of ␥ 7 causes loss of the Golf ␣ subunit, resulting in specific changes in cyclase activity in the striatum (77), reconstitution studies showing a preference of certain receptors for specific ␤␥ dimers (31, 70 -73), and results using small interfering RNA to knock down the ␤ 2 subunit in the J774.A1 macrophage line, showing loss of this subunit blunts the ability of the C5a receptor to stimulate a rise in intracellular Ca 2ϩ (76). Our own data show that dimers containing ␥ 11 support coupling of ␣ subunits to receptors very well (70), yet these dimers are very poor at regulating effectors such as PtdIns 3-kinase (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that increased rates of proliferation and levels of malignancy in colorectal tumour cells may be attributable to downregulation of one or more isoforms of GLS, accompanied by increased glucose metabolism (Turner and McGivan, 2003). GNG4 is a member of the G protein gamma subunits multigene family (Kleuss et al, 1993), which is required for coupling of the muscarinic receptor to voltage-sensitive calcium channels (Kalyanaraman et al, 1998). To investigate whether GNG4 has tumour suppressor activity, we transformed wild-type GNG4 into a RCC cell line with loss of GNG4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore this clonal cell line has both transient low-threshold calcium currents, and dihydropyridine-sensitive high-threshold calcium currents and inactivation of which is modulated by adenosine 3':5'-cyclic monophosphate (cyclic AMP) (Cohen & McCarthy, 1987;Kalman et al, 1988). High-threshold calcium currents in GH4C1 cells are also depressed by G-protein a-subunits liberated upon activation of somatostatin receptors (Luthin et al, 1992; Kleuss et al, 1993). In this study we describe the selective ability of hD2 and hD4, but not hD3 receptors, to couple to the depression of calcium currents in transfected GH4C1 cell lines.…”
Section: Introductionmentioning
confidence: 99%